When Harry met Sally [videorecording (DVD)] - Reiner, Rob; Crystal, Billy; Ryan, Meg (MGM Home Entertainment, 2001)
Romantic comedy that starts with the relationship between just-graduated-from-college Sally and Harry. They drive to New York together and find they dislike each other, but through the years develop a close friendship. The big question is can they sleep together and still love each other in the morning!